2022
DOI: 10.1155/2022/1489094
|View full text |Cite
|
Sign up to set email alerts
|

Bioprotection on Chardonnay Grape: Limits and Impacts of Settling Parameters

Abstract: Background and Aims. If bioprotection has already been proven to limit the development of spoilage flora on musts, its effectiveness against oxidation depends on the winemaking process. To optimize its application, this study analyzed the evolution of the chemical composition of the bioprotected musts and wines, according to different settling routes. Their impacts on the organoleptic characteristics of wines were also studied. Methods and Results. A bioprotected must was subjected to 6 different maceration ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Indeed, its efficiency was demonstrated when inoculated with H. valbyensis but was not found when inoculated with H. uvarum. These results may seem surprising in view of the previous results from the field trials, in which the bioprotective strain was shown to be established and to predominate over the indigenous flora, even when a high proportion of H. uvarum was present [ 10 , 53 , 54 ]. These results need to be confirmed on other strains belonging to these species.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Indeed, its efficiency was demonstrated when inoculated with H. valbyensis but was not found when inoculated with H. uvarum. These results may seem surprising in view of the previous results from the field trials, in which the bioprotective strain was shown to be established and to predominate over the indigenous flora, even when a high proportion of H. uvarum was present [ 10 , 53 , 54 ]. These results need to be confirmed on other strains belonging to these species.…”
Section: Resultsmentioning
confidence: 90%
“…A wide range of commercial active dry NS yeasts are currently sold by manufacturers as bioprotective yeasts, mainly from Metschnikowia and Torulaspora genera [ 8 ]. The efficiency of bioprotection was previously proven in field trials with a reduction in indigenous yeasts growth through the addition of bioprotection [ 9 , 10 , 11 , 12 , 13 , 14 ], without a thorough investigation of the physiological mechanisms involved. Numerous interactions occur in the microbial world and fall into two main groups: direct (cell–cell contact) or indirect interactions (nutrient competition, toxic compound production, quorum-sensing, enzymatic activity, etc.)…”
Section: Introductionmentioning
confidence: 99%
“… Main results on bio-protection obtained in field trials (From data published in journals for professionals and in Chacon-Rodriguez et al, 2020 ; Simonin et al, 2020 , 2022 ; Windholtz et al, 2021a , b,c ; Agarbati et al, 2023 ; Puyo et al, 2023 ). …”
Section: Bio-protection By Metschnikowia Pulcherrima ...mentioning
confidence: 99%
“…In white winemaking, a M. pulcherrima strain was tested on Chardonnay must using three temperatures (7°C, 12°C and 18°C) and two settling times (36 and 72 h) in order to determine the optimal conditions for a bioprotective effect ( Simonin et al, 2022 ). The results showed a considerable impact of temperature on the bioprotectant implantation.…”
Section: Bio-protection By Metschnikowia Pulcherrima ...mentioning
confidence: 99%
See 1 more Smart Citation